Specific in vitro cleavage of Mason-Pfizer monkey virus capsid protein: evidence for a potential role of retroviral protease in early stages of infection - Rumlová, Michaela; Ruml, Tomás; Pohl, Jan; Pichová, Iva (Virology, 2003)
Processing of Gag polyproteins by viral protease (PR) leads to reorganization of immature retroviral particles and formation of a ribonucleoprotein core. In some retroviruses, such as HIV and RSV, cleavage of a spacer peptide separating capsid and nucleocapsid proteins is essential for the core formation. We show here that no similar spacer peptide is present in the capsid-nucleocapsid (CA-NC) region of Mason-Pfizer monkey virus (M-PMV) and that the CA protein is cleaved in vitro by the PR within the major homology region (MHR) and the NC protein in several sites at the N-terminus. The CA cleavage product was also identified shortly after penetration of M-PMV into COS cells, suggesting that the protease-catalyzed cleavage is involved in core disintegration.
Keywords: Nucleocapsid; Virus Replication; Mason-Pfizer monkey virus; Amino Acid Sequence; Animals; Masonův-Pfizerův opičí virus; virové plášťové proteiny; COS buňky; sekvence aminokyselin; Endopeptidases; COS Cells; Capsid Proteins; nukleokapsida; zvířata; genové produkty gag; replikace viru; HIV-proteasa; HIV Protease; endopeptidasy; HIV-1; Gene Products, gag